St. Lucia : 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights St. Lucia's GDP growth, estimated to have reached 0.8 percent in 2016, down from 1.8 percent in 2015. Strong employment growth in agriculture and construction put a dent in unemployment, which declined to 20 percent in the third quarter of 2016. Youth unemployment also fell, but remains very high at 41 percent. GDP is projected to grow at 0.5 percent in 2017, driven mostly by continued strong performance in construction and agriculture. Higher import prices, including for oil, will cause inflation to rise temporarily and, together with weak tourism expenditures, will contribute to wider external imbalances.